Relationship between anthropometrics composition, specific field tests and throwing ball velocity of male team handball players: Technology for assessments tools of Qatar handball first professional l - Alneama, A.; Hermassi, S.; Jabnoun, M.; Chelly, M. S. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Anthropometric parameters, physical motor test, and throwing ball velocity have been identified as fundamental in order to determine the success of the performance in handball helping in the optimal design of physical fitness programs 1,2. This study examined the relationships between the physical fitness, anthropometry, and throwing ball velocity of first-division male team handball players in Qatar sate.